Odločanje nadzornega sveta - Zakšek, Kristijan (Podjetje in delo, 2019)
The main theme of the author''s work is the passing of resolutions by the supervisory board, comparing the Slovenian and German legal regulations in accordance with Article 257 of the Slovenian Companies Act (ZGD-1) and the 108th paragraph of the German Companies Act (AktG). The author points out some open questions, especially in Slovenian law. Some of these questions have not yet been dealt with by theory and case law. The German interpretation, which is also sometimes non-consistent, is presented. In accordance with the similarity of the German and Slovenian regulations, it is sensible to look for and give Slovenian law the same or similar interpretation as in the German law.